FEKTIVITAS METODE JARIMATIKA UNTUK MENGUKUR KUALITAS DALAM KETERAMPILAN NUMERASI KELAS II SD NEGERI PEBATAN 01 BREBES - Pradita, Firda; Laelia Nurpratiwiningsih; Tri Setiyoko, Didik (Fakultas Tarbiyah Institut Agama Islam Ngawi, 2024)
The main aim of this research is to determine the application of the jarimatics method in improving students learning outcomes in numeracy skills and to determine the obstacles in its application in class II at SDN Pebatan 01 Brebes. The approach taken in research uses a quantitative experimental approach. Effort techniques for collecting data by conducting observations and tests. The results obtained were that by using the Jarimatika method there was an increase in student learning outcomes in mathematics learning, where there were 25 students who had successfully completed the material with a percentage of 89%, while 3 students had not succeeded in completing it with a percentage of 11%.